Factors Affecting the Health Condition of the Elderly Living in Poverty in Nuevo León, Mexico - Carmona-Valdés, Sandra Emma (Población y Salud en Mesoamérica, 2015)
The purpose of this research was to investigate the influence of social, economic, structural, biological, and individual factor in the health status of elderly men and women who live within the polygons of poverty. It was studied the information of 549 individuals, from 70 to 104 years or more, through secondary data obtained from the evaluation of the Program of Care for the Elderly in Nuevo Leon. The central hypothesis of the research assumed the existence of social, structural, biological, and individual factors in men and women associated with health even in conditions of vulnerability. The regression results indicate a predictive relationship mainly to biological factors (limitation and suffering); physical activity and work are significant under certain conditions. In conclusion, the factors that influence the health status of the elderly in poverty are mainly biological: the studied social, structural, and individual factors do not represent a significant predictive relationship with the health condition within Nueva Leon polygons of poverty.